INOVASI LAYANAN DI PERPUSTAKAAN UMUM KOTA PEKANBARU - Rahman, Zio Andari; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Library service is a form of public service provided by the government to the public to provide information and knowledge through literacy reading material. Existing library services must of course follow the needs of the community and adjust the times, one of which is by innovating library services. With the presence of innovative library services in Pekanbaru City Public Library as a form of application of the pillars in the Smart City in Pekanbaru City, namely Smart People, it is expected to be able to increase the number of library visits and the level of cultural interest in reading. The purpose of this study is to find out how public library service innovation and find out what factors influence the innovation of library services. This study uses a purposive sampling technique with qualitative research types using a descriptive approach and the data needed both primary and secondary data obtained through observation, interviews and documentation and then analyzed based on research problems. The results of this study show that: Innovation in public library services in this study namely the mobile library, public reading park, iPekanbaru and Website has not been running optimally. Factors that influence the innovation of public library services are human resources, facilities and infrastructure as well as the community. Keywords: Innovation, Public Services, Library Services, Public Library.